Athlete Self-Efficacy Scale Indonesian Version Using Bayesian Confirmatory Factor Analysis: Construct Validity Testing - Mubarak, Fadhil; Tasyafa, Fadia; Wulan, Nabella Ayu; Kusumawardhani, Dianti Endang (Journal of Educational, Health and Community Psychology, 2025)
Self-efficacy is a psychological construct that plays a crucial role in athletic achievement, as it reflects athletes’ belief in their ability to face challenges in both training and competition. This study aimed to examine the construct validity of the Athlete Self-Efficacy Scale (ASES) in the Indonesian context. A Bayesian-based Confirmatory Factor Analysis (CFA) approach was applied to data from 316 athletes (158 male, 158 female) representing 33 sports disciplines across 21 provinces. The results confirmed that a four-factor model—Sport Discipline Efficacy, Psychological Efficacy, Professional Thought Efficacy, and Personality Efficacy—provided the best fit (BRMSEA = 0.073, BCFI = 0.926, BTLI = 0.910, BNFI = 0.881), indicating strong construct validity and good reliability. These findings demonstrate that the Indonesian version of ASES is a valid and adaptable measurement tool for assessing athletes’ psychological resources. However, this study has several limitations, including its cross-sectional design, the absence of measurement invariance testing, and the relatively homogeneous cultural background of participants, which may restrict generalizability. Future studies should adopt longitudinal designs and test invariance across gender, age, and sport types to strengthen the instrument’s applicability. Despite these limitations, the validated scale carries significant social implications, offering coaches, sport psychologists, and policymakers a culturally relevant tool to design interventions, enhance athlete development programs, and foster mental resilience in Indonesian athletes.